O‘ZBEK TILIDAGI RETRONIMLARNING TEMATIKASI - Xolmonova Sadoqat (International Scientific and Current Research Conferences, 2023)
It is no secret that the development of a language is closely connected with the life of society. Especially now, when science and digital technologies are rapidly developing, the vocabulary of the Uzbek language continues to be enriched with new retronyms, and this situation is reflected in the speech of people in everyday life. The need to study this phenomenon is increasing due to the fact that the vocabulary of native speakers is enriched with new concepts every day, and we are increasingly using retronyms. This article is devoted to the study of retronyms in the Uzbek language. To this day, the topic of retronyms is one of the relatively little-studied areas. The issue of retronyms in the world and Uzbek linguistics is one of the important issues to be comprehensively studied. Therefore, in our article, we tried to reflect on retronyms in the Uzbek language and their subject matter